Patient Medication Use: Interpreting the Results of a Patient Medication Safety Survey by Phase I Immersion Pharmacy Students - Michael Li; Claudia F Ortiz Lopez; Nita Johnston (University of Minnesota Libraries Publishing, 2016)
A medication safety survey was created during our first year pharmacy rotations in order to assess and gain insight to how safe patients are with their medications at home. The patient population was from the nursing units and emergency department of Moses Cone Hospital in Greensboro, NC. The survey questions covered the topics including how the patients take their medications, medication storage, medication disposal, as well as medication adherence.   Type: Student Project